The big stink - Lubar, David (Lubar, David. Nathan Abercrombie, accidental zombie, 2010)
A mold problem disrupts things at Nathan's school and his class is forced to share a space with first and eighth graders including Rodney the bully's older brother. Meanwhile, Nathan notices that a putrid smell is following him around and tries to discover its source.